2016
DOI: 10.15255/kui.2016.005
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Preparation Methods of Graphene Nanocomposites for Low-Temperature Fuel Cells and Lithium-Ion Batteries

Abstract: Because of its unique two-dimensional structure, huge specific surface area, high electrical conductivity, and other excellent performances, graphene has shown great potential for application in catalysis, electronics, sensors, energy storage, and other areas. Especially, graphene nanocomposites have been found to be promising catalyst support for low-temperature fuel cells, and as anode nanomaterials for high reversible capacity and excellent rate capability for lithium-ion batteries, which has triggered a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Carbon nanomaterials (CNMs) such as graphene, carbon nanotubes (CNTs), and nanofibers possess extraordinary physical, chemical, and mechanical properties for applications in various fields to improve life quality. , CNMs have attracted considerable research interest to optimize and expand their applications, especially with respect to energy and environmental applications such as energy conversion (i.e., solar cells and fuel cells), energy storage (i.e., supercapacitors and batteries), and environmental remediation (i.e., removal of heavy metals and organic contaminates from water and soils). When applied to energy conversion and storage, CNMs have shown excellent electrochemical stability and charge transfer/storage properties. In addition, CNMs are excellent adsorbents for various organic and inorganic contaminants, including antibiotics, PAHs, organic pesticides, and heavy metals. It has also been reported that modification of CNMs can introduce new structures to further enhance their physicochemical properties. Both CNMs and modified CNMs are promising high-performance structural and multifunctional materials for energy and environmental applications.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanomaterials (CNMs) such as graphene, carbon nanotubes (CNTs), and nanofibers possess extraordinary physical, chemical, and mechanical properties for applications in various fields to improve life quality. , CNMs have attracted considerable research interest to optimize and expand their applications, especially with respect to energy and environmental applications such as energy conversion (i.e., solar cells and fuel cells), energy storage (i.e., supercapacitors and batteries), and environmental remediation (i.e., removal of heavy metals and organic contaminates from water and soils). When applied to energy conversion and storage, CNMs have shown excellent electrochemical stability and charge transfer/storage properties. In addition, CNMs are excellent adsorbents for various organic and inorganic contaminants, including antibiotics, PAHs, organic pesticides, and heavy metals. It has also been reported that modification of CNMs can introduce new structures to further enhance their physicochemical properties. Both CNMs and modified CNMs are promising high-performance structural and multifunctional materials for energy and environmental applications.…”
Section: Introductionmentioning
confidence: 99%